Nietzsche e il nichilismo francese - Campioni, Giuliano (Bollettino Filosofico, 2015)
The concept of “Nihilism” is already present in Nietzsche’s earliest writings as a radicalization of Schopenhauer’s pessimism. However, in Nietzsche’s notes of the ’80s, the terms “nihilistic”, “nihilism” assume a theoretical centrality, above all, starting from the autumn of 1886, in connection with the concept of “will to power”. The very term “nihilism” and the complexity of the issue become increasingly central compared to French culture, particularly with writers like Richepin, Brunetiere, and especially Paul Bourget. Bourget examined and diagnosed as "psychologist" the many signs of nihilism in the most significant cultural attitudes of the time. He was able to describe, when they made their very appearance, the widespread twilight of values, the disease that paralyzes the will of the West, the sense of “the fall of civilization”. In the end, his analyses bring Bourget to approach the care of "social disease" by requiring, as the sole remedy, the Catholic religion and traditional values.